The Effect of State Mandates on Student Performance - Rhine, Sherrie L. W. (American Economic Review, 2016)
In recent years, several states have initiated some form of economic instruction mandate in their high school curriculum. Although it may be argued that students more knowledgeable about economics should perform better as consumers and citizens, it is not clear that a state-imposed mandate will result in an optimal level of economic education. Accordingly, the purpose of this study is to investigate whether or not performance differences exist between students in a mandated and nonmandated environment.